PERKAWINAN NYEBURIN BERBEDA AGAMA DITINJAU DARI HUKUM ADAT BALI (Studi Kasus Di Banjar Dakdakan, Desa Pakraman Kelaci Kelod, Kabupaten Tabanan) - ADNYANA, I WAYAN PUTRO; WINDIA, I WAYAN; SUDANTRA, I KETUT (Kertha Wicara : Journal Ilmu Hukum; Vol 1 No 01 (2012), 2012)
Indigenous people in Bali majority embraced Hinduism, who hold patrilinealsystem. In this connection the kinship system appears to have strong adhesive ofthe Hindu religion, which gives place to the importance of descendants (sons) in afamily. Adopted patrilineal kinship system, The boys which is future expectationsof family as the successor of offspring in the family. However, these expectationsmay be different, when the boy was can not be born and even there a marriedcouple a completely not able to produce offspring. In these circumstances,Hinduism with the customary law in Bali appear as the "antidote" namely by theway for hold line-progressors descent or family among others by the way raised asingle daughter as SentanaRajeg (purusa/male) a marriage done with nyeburinmarriage.The system is can be considered as exception of patrilineal system infamily law in Bali, but when viewed more in-depth essentially not so is, becausethe woman who have made nyeburin marriage have the right as heir in his family.In fact, it is not always easy to seek a man who would nyeburin mating moreoverthe same religion. Therefore, the nyeburin marriage different religions it mayhappen like that occurred in DakdakanBanjar, KelaciKelodPakraman village,Tabanan regency, found three cases nyeburin marriage which is not done betweenfellow Hindu, but done between men other Hindus (Muslims and ChristiansCatholic) as parties nyeburin, while the keceburin are women which Hindu
Keywords: Nyeburin Marriage, Different Religions, SentanaRajeg, Purusa (Male), Bali Customary Law.